1993
DOI: 10.1111/j.1365-3083.1993.tb01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Binding Specificities of the Homology Regions (Domains) of Protein A

Abstract: Protein A binds immunoglobulins and it has two target structures, one in Fc gamma (CH) and the other in selected VH regions. The protein has five homology regions (domains), A, B, C, D, and E. Fc-binding and VH-binding have been reported to be non-competitive, suggesting that different domains are responsible for the binding of the two ligands. On the other hand, all five domains have been reported to bind Fc. I studied binding of different immunoglobulins by protein A or its domain B (rBB). The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…Previously, domains E and/or D have been suggested to be responsible for the main Fab binding of protein A [8, 9, 42]. Our data does not support this hypothesis as domains A, B, and C in our experiments all bind Fab with similar strength as domains E and D. In conclusion, this work has demonstrated that all five native SPA domains E, D, A, B and C show affinity for both Fab and Fc.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Previously, domains E and/or D have been suggested to be responsible for the main Fab binding of protein A [8, 9, 42]. Our data does not support this hypothesis as domains A, B, and C in our experiments all bind Fab with similar strength as domains E and D. In conclusion, this work has demonstrated that all five native SPA domains E, D, A, B and C show affinity for both Fab and Fc.…”
Section: Discussioncontrasting
confidence: 97%
“…However, the binding analysis of separate monovalent protein A fragments to F(abP) P and to the scFv gave the unexpected result that domain B clearly binds Fab whereas the very similar domain Z shows only little or no binding activity. Although the observed weak binding for domain Z to Fab is in accordance with earlier results [40], a stronger Fab binding of domain B is observed in this study as compared to precious ¢ndings [8,40]. However, data such as shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A relatively weak binding signal was observed for the human Fab fragment. Less common is the ability of Protein A to bind the Fab fragment of immunoglobulins, especially the Fab heavy chain V H 3 family [ 7 , 8 , 43 , 44 ]. It was found that both Fc and Fab fragments bind to Protein A in a noncompetitive way and that they use the same Ig-binding domains, but different epitopes inside of these domains [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that domains A, D and/or E contain at least one site necessary for Fab binding. In one study rBB exhibited binding to an isolated recombinant VH3 [17], whereas in another study, the same recombinant fragment B failed to bind five monoclonal antibodies bound by SPA via the VH region [28]. The basis for these different findings remains unresolved.…”
Section: Staphylococcal Protein Amentioning
confidence: 96%